Potential and economic feasibility of green hydrogen production from hydropower in Honduras - Zúniga-Paguada Cristian; Reyes-Duke Alicia María (E3S Web of Conferences)
Due to the need of limiting renewable energy generation because of the intermittency of solar and wind energy in Honduras, it has been decided to utilize thermal power plants to generate electricity, thereby aiding in the stabilization of the national electrical grid. Alternatively, relying more heavily on hydroelectric power plants with reservoirs would require their full availability and greater effort, which could lead to increased wear on the turbines and pose risks to their regular operation. Thermal power plants, by their nature, release greenhouse gases (GHG) into the atmosphere, primarily in the form of carbon dioxide, which is harmful to health and a global concern due to recent issues with global warming. Given the daily limitations of renewable generation, using green hydrogen as an energy vector for future reintegration into the electrical grid presents a more renewable solution. This alternative also offers potential applications such as electromobility. Through potential and economic analysis, it has been determined that producing hydrogen from hydroelectric energy in Honduras could yield 3,204,379.12 kg of hydrogen annually by fully harnessing available energy. The analysis also shows economic feasibility with a cost-benefit ratio of 1.02 over a 30-year project timeframe, with a return on investment estimated of 3.29 years.